Exploring Immune Responses through Dynamic Modeling of Cell-Immune Interactions in Viral Infection and Vaccination - Kwang Su Kim; Il Hyo Jung; Jong Hyuk Byun (Complexity)
Infectious diseases pose a significant threat to global health, necessitating the development of effective vaccination strategies. This study examines the dynamics of viral infections and immune responses, with a particular focus on the roles of antibodies and CD8+ T cells induced by vaccination. Through a mathematical model, we explore the intricate interactions between host cells and viruses to assess the impact of vaccination on viral replication. Our findings align with experimental results, demonstrating that vaccination substantially enhances immune responses and reduces viral replication. The contributions of both antibody and CD8+ T cell responses are shown to be vital for achieving optimal vaccine efficacy. The model’s predictions, validated against experimental observations, emphasize the need to incorporate mechanisms that induce robust immune responses in vaccine design. This study underscores the critical role of mathematical modeling in understanding immune dynamics and in refining vaccination strategies to develop more effective treatments against viral infections.